Development and application of deformation monitoring system for lanslide at Funchunjiang Dam. Issue 339 (November 2014) - Yao, L. B.; Sun, H. L.; Zhu, L. X.; Zhou, Y. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Under the background of the landslide deformation monitoring of the left mountainside at Fuchunjiang Dam, we developed an automatic Landslide Deformation Monitoring System (LDMS) based on the TCA2003 surveying robot. Our LDMS extended the applications of TCA2003 in deformation monitoring by using GEOCOM serial-port functions. The system has the following features: automatic multiple observation sets measuring, automatic field data sheets generating, hydrograph plotting and deformation analysing. The new system had been developed and implemented under the environment of Visual C++ 6·0. The system has simpler operations and stronger practical applicability, compared with previous landslide deformation monitor methods. Based on analysis of the coordinates of Leftpt point on the sliding mass of left mountainside on Fuchunjiang Dam, displacement occurred in recent years, the whole monitoring of the sliding mass is essential. The analysis of the data achieved by LDMS showed that the sliding mass had no clear uniform deformation, and each part of the sliding mass was noticeably different in the slipping speed in the landslide direction. Hence, regular monitoring is essential to prevent the sliding mass from local landslides.